Personal Hygiene Practices and Morbidity Pattern among A Tribal Primary School Children Of Maharashtra - Ashish Wasudeo Khobragade1 , Ninad Nagrale2, Mohd. Junaid1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Scholastic performance of the child depends upon the overall health of the child. Methods:A cross sectional study was conducted among 162 tribal school children. Results: Prevalence of anaemiawas 54.9%. Second most common morbidity was dental caries (31.48%) followed by underweight (27.77%)Head louse infestation was common among girl students. Conclusions: Most common morbidities presentamong primary school children of a tribal school were anaemia, dental caries, underweight and refractiveerrors. Girl students had better hygiene than boys.